Means of Securing the Preservation of Lawyer‘s Secrecy Under the Legislation of Uktaine - Заборовский, Виктор Викторович Викторович (Teisė, 2018)
[full article in Russian; abstract in English] Article is devoted to the definition of the essence of means of securing the preservation of the lawyer’s secret. Particular attention is paid to the legal regulation of guarantees that indicate the existence of the witness immunity of a lawyer and guarantees during the search or inspection of the home, other possession of the lawyer, the premises where he/she performs advocacy.